Isolation and characterization of bacteria associated with gastroenteritis in weaned piglets - Atulya M (Department of Veterinary Microbiology, College of Veterinary and Animal Sciences, 2009)
Gastroenteritis is a leading cause of morbidity and mortality in piglets. A number of factors are involved in post weaning diarrhoea in piglets. A comprehensive study was performed to examine the incidence, bacterial etiology, drug sensitivity, plasmid profile and pathogenicity of the bacteria isolated from weaned piglets with gastroenteritis prevalent in and around Kerala Agricultural university. Samples were taken only from piglets with diarrhoea that had not been previously treated with antibiotics. Rectal swabs were collected from live diarrhoeic piglets and intestinal contents, pieces of jejunum, ileum, colon, mesenteric lymph nodes, liver, spleen and stomach were collected during post mortem examination after taking all sterile precautions. Isolation of causative bacteria was made by culturing on Brain Heart Infusion Agar, Mac Conkey agar, Mannitol Salt agar, Blood agar, Brucella agar and Cooked Meat medium. The identification of isolates was carried out as per standard protocols. All the procedures of biochemical testing were followed as described by Barrow and Feltham (1993). For classification of Staphylococcus isolates, a system suggested by Baird Parker (1965) was considered. A total of 53 bacterial isolates were identified to species level from 82 samples tested for pathogens. Six different microorganisms were encountered in this study, with Escherichia coli being dominant, followed by Pseudomonas aeruginosa, Staphylococcus subgroups BPIII and BPV, Serratia fonticola, Salmonella typhimurium and Aeromonas hydrophila. Thirteen different serotypes of E. coli were encountered, with O69 being dominant and the others were O38, O5, O84, O132, O80, O79, O56, O41, O25, O109 and O103 and two were untypable. Majority of the isolates exhibited multidrug resistance. Plasmid profile of the Gram negative isolates were determined and 80.43 per cent were found to bear plasmids. Pathogenicity of the isolates was determined by performing in vivo mice pathogenicity test.